Screening Criteria Improve Access to Palliative Care in the PICU*. Issue 8 (August 2016) - Lutmer, Jeffrey E.; Humphrey, Lisa; Kempton, Tanya Maria; Moore-Clingenpeel, Melissa; Ayad, Onsy
Abstract : Objectives: To test the ability of palliative care screening criteria to improve access to palliative care services in the PICU and examine the association between palliative care team involvement and ICU and hospital length of stay. Design: Prospective interventional quality improvement study. Setting: PICU at a quaternary academic medical center. Patients: All patients admitted to the PICU who met criteria for palliative care referral over a 9-month period. Intervention: Consensus palliative care consultation criteria were created by pediatric critical care medicine and palliative care providers, and palliative care referral was encouraged for all PICU patients meeting criteria. Measurements and Main Results: Palliative care referral rates increased significantly after screening criteria implementation. We identified 100 patients who were eligible for palliative care services, and referrals were made for 70 patients (70%). Patients were divided into three groups based on palliative care status: patients new to the palliative care team, patients with an existing palliative care relationship, and patients who did not have a palliative care referral. By the end of study, patients who had an existing relationship with the palliative care team were more likely to still be alive and to have limitations of medical interventions in place, whereas patients who did not have a palliative care referral were more likely to be deceased and to have died in the PICU. After correcting for other factors, including severity of illness, patients who were new to the palliative care team experienced greater delay in palliative care referral and had significantly longer PICU and hospital length of stay than those who were already known to the palliative care team. Conclusions: Palliative care screening criteria are effective tools for improving access to palliative care services in the PICU; however, widespread adoption may produce a significant increase in palliative care demand. The association between an existing palliative care relationship and reduction in resource utilization deserves further investigation as does the perceived benefit of palliative care involvement in the patient, family, and staff experience.